Influência do diâmetro nas taxas de sobrevivência de implantes curtos e extra-curtos : revisão sistemática e meta-análise - Zanettini, Leonardo Matos Santolim (2022)
Aim: To systematically assess the current dental literature comparing the relation between the diameter length of short and ultra-short dental implants. Material and Methods: Two reviewers searched PubMed, Embase, Cochrane and Scopus were carried out, in addition to manual search and grey literature search w in order to find those studies that were not published on journals indexed on the principal databases. Results: Twenty four clinical studies from the 1962 articles initially identified met the inclusion criteria for the qualitative analysis. A total of 1.630 extra-short dental implants was included. The comparison between the relationship of diameter and length aimed to verify the failures rates in different types of short implants. The width was classified in 3 groups: Narrow (from 3.3–3.5 mm); Regular (from 3.75–4.5 mm) and Wide (from 4.8–6.5 mm). Each implant was correlated with each respective implant length and width group. On the narrow diameter implants group, a total of 68 implants with 6 mm length were analyzed. No failures were recorded. On the regular diameter implants group, 1.298 implants were recorded. A total of 50 failures were found. On the wide diameter implants group, 264 implants were analyzed. Conclusions: In conclusion, within the limitations of the current review, there is no evidence that a short or ultra-short implant has higher survival rates if it is of a wide diameter. In fact, with modern implant designs, the opposite may be true. Future studies with better control groups are necessary to bring stronger evidence to this concept.